Safety of electromagnetic factors for the workplace equipped with personal computers in residential premises - Yu. G. Ryabov; N. M. Legkiy; G. V. Lomaev (Российский технологический журнал)
Objectives. The aim of this paper is to analyze the electromagnetic safety of 50Hz industrial frequency electrical networks in residential buildings when using workplaces equipped with personal computers (PCs), as well as to develop recommendations on reducing the impact of levels of industrial frequency electromagnetic fields on human health in residential premises.Methods. Electromagnetic fields in residential premises with the single-phase TN mode industrial frequency power supply system regulated by the Rules of Electrical Installations Design were measured and calculated in accordance with Russian and international legislative documents.Results. It was established that electromagnetic fields induced by TN networks in workplaces equipped with PCs might increase significantly and even exceed the maximum permissible level of 25 V/m and 0.25 μT recommended by Sanitary and Epidemiological Standards. Residential buildings are not subject to the requirements of the Energy Supervision services; therefore, any unprofessional modification of electrical networks in residential premises, including the use of unapproved extension cords, may result in sparking, high-frequency harmonics, and, in turn, conditions which impact human health, as well as electric injures, fires, and gas explosions.Conclusions. It has been shown that IT (TT) mode symmetrical two-phase electrical networks may function efficiently for decades without accidents and effects of industrial frequency electromagnetic field on humans, as they are used in medical institutions, defense enterprises, and state institutions. Thus, legislative transition to installing IT (TT) systems in residential buildings, replacement of existing TN power supply systems with IT (TT) system, and legislative strengthening of requirements for household protection and commutation devices, may also be required to reduce man-made disaster risks in residential buildings.